1986
DOI: 10.1111/j.1442-9071.1986.tb00026.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable Sutures in Strabismus Surgery: A Personal Series of Cases

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In the study by Weston et al (n = 201 consecutive patients), just 40% of cases required suture adjustment, while the remaining 60% were simply tied off [25]. Agnello et al reported a necessity for adjustment in 62.3% of their AS strabismus surgeries (48/77 patients) [26]. Pratt-Johnson et al reported 48.2% (123/255) of patients required adjustment in AS surgery cases [27].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Weston et al (n = 201 consecutive patients), just 40% of cases required suture adjustment, while the remaining 60% were simply tied off [25]. Agnello et al reported a necessity for adjustment in 62.3% of their AS strabismus surgeries (48/77 patients) [26]. Pratt-Johnson et al reported 48.2% (123/255) of patients required adjustment in AS surgery cases [27].…”
Section: Discussionmentioning
confidence: 99%